The essential tensionbetween leadership and power when leaders sacrifice groups goals for the sake of self-interest.[article]. - Maner, Jon K.
Throughout human history, leaders have been responsible for helping groups attain important goals. Ideally, leaders use their power to steer groups toward desired outcomes. However, leaders can also use their power in their service of self-interest rather than effective leadership. Five experiments identified factors within both the person and the social context that determine whether leaders wield their power to promote group goals versus self-interest. In most cases, leaders behaved in a manner consistent with group goals. However, when their power was tenuous due to instability within the hierarchy, leaders high (but not low) in dominance motivation prioritized their own power over groups goals: They withheld valuable information from the group, excluded a highly skilled group member, and prevented a proficient group member from having any influence over a group task. These self-interested actions were eliminated when the group was competing against a rival outgroup. Findings provide important insight into factors that influence the way leaders navigate the essential tension between leadership and power.
Keywords: Leadership; Power; Individual differences; Dominance; Motivation